HUBUNGAN KEPERCAYAAN DIRI DENGAN KEMANDIRIAN BELAJAR PESERTA DIDIK KELAS VIII DAN IX DI SMPN 1 RANAH BATAHAN - Ainul Husna; Suryadi; Yasrial Chandra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low level of self-confidence among some students, which affects their learning independence, such as hesitation in answering questions, dependence on peers, and lack of initiative in completing tasks. This research aims to describe the level of students’ self-confidence, describe their learning independence, and examine the relationship between self-confidence and learning independence of eighth and ninth grade students at SMP Negeri 1 Ranah Batahan. The study employed a quantitative approach with a correlational research design. The population consisted of 84 students, all of whom were selected as research samples using a total sampling technique. Data were collected through questionnaires and analyzed using Pearson Product Moment correlation. The results showed a positive and significant relationship between self-confidence and students’ learning independence, with a correlation coefficient of 0.499 and a significance value of 0.000 (p < 0.05). This indicates that higher levels of self-confidence are associated with higher levels of learning independence. Self-confidence plays an important role in shaping students’ independent learning attitudes; therefore, guidance and counseling services are needed to help improve students’ self-confidence in order to support their learning independence.